Land Registration Policy and the Absence of Gender Justice in North Sumatra - M. Nazir Salim; Trisnanti Widi Rineksi; Rohmat Junarto; Dwi Wulan Pujiriyani; Westi Utami; Rosye C. Vilanova; Dian Aries Mujiburohman; Kusmiarto Kusmiarto; Mujiati Mujiati; Tatag Bagus Narendra; Annisa Nur Aisyah; Lutfia Nursetya Fuadina; Sarjita Sarjita; Millennia Duta Ramadhana; Berlian Imani Putri (Marcapada: Jurnal Kebijakan Pertanahan, 2026)
Gender inequality in formal land ownership remains evident, particularly within indigenous communities, even though land rights are legally guaranteed equally for all citizens. This study evaluates the distribution of land ownership based on gender and to analyze the effectiveness of land registration programs, particularly the Complete Systematic Land Registration program, in North Sumatra Province. Using a mixed-methods approach, the research combines legal ethnography with quantitative analysis. Data were collected through field observations, focus group discussions, interviews with relevant stakeholders, and a literature review. Geographic Information Systems (GIS) were used to visualize the spatial distribution of land ownership. legal ethnography examined tenure systems and legal-cultural practices in the study sites. The research was conducted in two locations representing different socio-spatial contexts: Samosir Regency (rural-traditional) and Deli Serdang Regency (sub-urban). The findings reveal gender inequality in land ownership. Spatial analysis indicates that men dominate land ownership with 50.52%, while women account for 38.76%, and the remaining 10.72% of the data lack gender identification. The legal ethnographic analysis further shows that the patrilineal system and administrative barriers in land registration—such as the absence of gender-disaggregated data—continue to sustain the marginalization of women in obtaining equal land rights. The study concludes that regional transitions from rural to sub-urban settings provides greater opportunities for women to access land ownership. However, current government programs remain gender-neutral in design, which may inadvertently reinforce existing inequalities.